Integrated Phone Counselling and Text Messaging Services at Quitlines: An Acceptability Study. (1st May 2014) - Abroms, Lorien C.; Carroll, Philip; Boal, Ashley L.; Mendel, Judith; Carpenter, Kelly M.
Abstract : Introduction: With evidence to support the use of text messaging for smoking cessation, some quitlines in North America have incorporated text messaging into their service offerings. Aims: This study sought to evaluate whether integrated phone counselling and text messaging services are acceptable to quitline callers, and to identify strategies for improving text messaging services in the context of a quitline. Methods: Thirty-five adult callers of the New Mexico state quitline who had enrolled in multi-call phone counselling and Text2Quit, a text messaging programme, were interviewed by phone. Interviews assessed use and acceptability of the phone counselling and text messaging interventions. Results: Use of phone counselling and text messaging was generally high among participants. While most participants reported that they would highly recommend Text2Quit (75.8%) or phone counselling (78.8%) individually, a relatively higher proportion indicated they would highly recommend the combined services (93.9%). Suggestions for improvement focused on increased customisation and personalisation. Conclusions: This study provides preliminary evidence for the acceptability of integrated phone counselling and text messaging services. Research is needed that explores the impact of these widely-used integrated services on smoking cessation.